2015
DOI: 10.1016/j.jphs.2015.08.004
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacological characterization of the involvement of protein kinase C in oscillatory and non-oscillatory calcium increases in astrocytes

Abstract: Evidence increasingly shows that astrocytes play a pivotal role in brain physiology and pathology via calcium dependent processes, thus the characterization of the calcium dynamics in astrocytes is of growing importance. We have previously reported that the epidermal growth factor and basic fibroblast growth factor up-regulate the oscillation of the calcium releases that are induced by stimuli, including glutamate in cultured astrocytes. This calcium oscillation is assumed to involve protein kinase C (PKC), wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 27 publications
0
8
0
Order By: Relevance
“…These observations are consistent with the data reported by Morita et al . () showing that inhibition of PKC by a series of pharmacological inhibitors converts astrocytic calcium signalling from an oscillatory to a sustained or non‐oscillatory calcium response (Morita et al . ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are consistent with the data reported by Morita et al . () showing that inhibition of PKC by a series of pharmacological inhibitors converts astrocytic calcium signalling from an oscillatory to a sustained or non‐oscillatory calcium response (Morita et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…() showing that inhibition of PKC by a series of pharmacological inhibitors converts astrocytic calcium signalling from an oscillatory to a sustained or non‐oscillatory calcium response (Morita et al . ). Moreover, cells exposed to a selective PKCε activator also showed a loss of calcium oscillations and exhibited progressive desensitization.…”
Section: Discussionmentioning
confidence: 99%
“…With Fss increased, [Ca 2+ ] i patterns changed from perfection oscillations, to combined oscillations at the plateau, and to homogeneous peak‐plateau patterns. Biochemical stimuli could result in similar phenomena, suggesting that strong stimuli leaded to more non‐oscillatory [Ca 2+ ] i increase while slight stimuli induced more [Ca 2+ ] i oscillations, such as in ATP‐stimulated Hela cells and glutamate‐stimulated astrocytes . Cell density also contributed to [Ca 2+ ] i patterns that high cell density increased [Ca 2+ ] i oscillations in non‐excitable cells .…”
Section: Discussionmentioning
confidence: 95%
“…Morita et al have shown that blockade of PKCs by a series of pharmacological inhibitors converts glutamate-induced Ca 21 oscillations to sustained or nonoscillatory responses in astrocytes (Morita, Nakane, Maekawa, & Kudo, 2015). Morita et al have shown that blockade of PKCs by a series of pharmacological inhibitors converts glutamate-induced Ca 21 oscillations to sustained or nonoscillatory responses in astrocytes (Morita, Nakane, Maekawa, & Kudo, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The mobilization of Ca 21 by mGluR5 is largely dependent on the initial release of Ca 21 from intracellular stores, suggesting that downstream signaling effectors of mGluR5 could be implicated in the altered mGluR5 signaling in hSOD1 G93A astrocytes. Morita et al have shown that blockade of PKCs by a series of pharmacological inhibitors converts glutamate-induced Ca 21 oscillations to sustained or nonoscillatory responses in astrocytes (Morita, Nakane, Maekawa, & Kudo, 2015). More specifically, reduced expression of the PKCE isoform has been shown to convert the mGluR5 oscillatory profile into a peakplateau type response (Bradley & Challiss, 2011;Vergouts et al, 2017).…”
Section: Discussionmentioning
confidence: 99%